Direct seeding of mass-cultured coral larvae is not an effective option for reef rehabilitation - Edwards, Alasdair J. (2015)
Large-scale rearing of coral larvae during mass spawning events and subsequent direct introduction of competent larvae onto denuded reefs (‘larval seeding’) has been proposed as a low-tech and affordable way of enhancing coral settlement and hence recovery of degraded reefs. While some studies have shown positive short-term effects on settlement, to date, none have examined the long-term effects of larval seeding for a broadcast-spawning coral. Here, we test whether larval seeding significantly increases coral recruitment rates both in the short (5 wk) and longer (~6 mo to 1 yr) term. Larvae of Acropora digitifera were reared ex situ, and ~1 million larvae were introduced to 7 artificial reefs (ARs) while 7 others were left unseeded. Settlement tiles deployed on both seeded and control ARs were retrieved for examination 5 and 30 wk after seeding. In addition, the presence of visible coral recruits on the AR surfaces was monitored before and for ~13 mo post-seeding. Density of acroporid spat was significantly higher on seeded tiles than on controls 5 wk after seeding, but this effect had vanished by 30 wk. Comparison of the densities of new visible Acropora recruits between seeded and control ARs showed no significant difference ~13 mo after seeding. Larval seeding therefore had no long-term effect due to high post-settlement mortality (which appeared to be density-related). Results suggest that reef-rehabilitation methods that aim to harness coral sexual reproduction might better focus on rearing juveniles through early post-settlement mortality bottlenecks.